The Perception of Death in Cultural Tourism - Tanaś, Sławoj (Turyzm/Tourism, 2008)
The author’s aim is to present the role of death (its conceptions, symbolism and effects) in forming social tourist space. The author presents the history of the perception of death and quotes examples of death-related sites which are interesting from a tourist point of view. He also attempts to answer the question why tourists visit places associated with death.